Impact on CYP19A1 activity by mutations in NADPH cytochrome P450 oxidoreductase. Issue 165 (January 2017) - Flück, Christa E.; Pandey, Amit V.
Graphical abstract: Highlights: Variations in POR affect multiple cytochrome P450 activities. Mutant POR affects CYP19A1 activities. CYP19A1 disruption due to POR mutations may cause disordered steroidogenesis. Abstract: Cytochrome P450 aromatase (CYP19A1), in human placenta metabolizes androgens to estrogens and uses reduced nicotinamide adenine dinucleotide phosphate through cytochrome P450 oxidoreductase (POR) for the energy requirements of its metabolic activities. Mutations in the human POR lead to congenital adrenal hyperplasia due to loss of activities of several steroid metabolizing enzymatic reactions conducted by the cytochrome P450 proteins located in the endoplasmic reticulum. Effect of POR mutations on different P450 activities depend on individual partner proteins. In this report we have studied the impact of mutations found in the POR on the enzymatic activity of CYP19A1. We expressed wild type as well mutant human POR proteins in bacteria and purified the recombinant proteins, which were then used in an in vitro reconstitution system in combination with CYP19A1 and lipids for enzymatic analysis. We found that several mutations as well as polymorphisms in human POR can cause reduction of CYP19A1 activity. This would affect metabolism of estrogens in people with variations of POR allele. The POR mutants Y181D and R616X were found to have no activity in supporting CYP19A1 reactions. The POR mutations Y607C and delF646 showed a loss of 60–90% activity and two polymorphic forms of POR, R316W and G413S showed similar to WT activity. One POR variant, Q153R had almost double the activity of WT. Loss of CYP19A1 activity may contribute to disordered steroidogenesis in female patients with POR mutations as well as in mothers with POR variants carrying a male child.